Evaluation of Emotions as an Appreciation of the Confidence Generated During Learning Veterinary Surgery (2023)
Veterinary surgery students' perceived confidence was assessed through negative and positive emotions after a series of surgical sessions. Surveys were administered to 80 veterinary surgery students after the surgical sessions were completed. Six negative emotions and five positive emotions were assessed. Data of negative and positive emotions were analyzed on a Likert scale. Surgery was performed on dogs in the academic unit's operating rooms. Surgeries of the upper respiratory tract, digestive tract, urinary tract, reproductive tract, and musculoskeletal system were included. The surgical procedures performed allowed to generate different emotions since the students acquired different surgical skills in manipulating soft and hard tissues of the mentioned organs and systems. Tension stood out in each of the surgical sessions performed, the other negative emotions showed movements depending on the type of surgery, thus the first session marked more to certain emotions, continuing afterward stable, except in the surgical session in the musculoskeletal system. The positive emotions showed a tendency to taste, desire and expectation to experience the action of the basic principles of surgery.